2017
DOI: 10.1080/16000889.2017.1328945
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of sulphur and nitrogen in Europe 1900–2050. Model calculations and comparison to historical observations

Abstract: As a contribution to an EU project which dealt with the effects of climate change, air pollution impacts and ecosystems, two different atmospheric chemical transport models were used to simulate the depositions of acidifying and eutrophying pollutants over Europe for the period 1900-2050. Given the unavoidable uncertainties in the historical inputs to these simulations (emissions, meteorology), we generated a new and unique data-set for the purposes of model evaluation; comprising data from the European Air Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(119 citation statements)
references
References 69 publications
(109 reference statements)
5
110
1
3
Order By: Relevance
“…This set-up (EMEP + RCA3) is also used by Langner et al (2012a), Simpson et al (2014a), Tuovinen et al (2013), Franz et al (2017) and Engardt et al (2017), in which further details and model evaluation can be found. Unfortunately, the threedimensional RCA3 data needed by the EMEP model were not available prior to 1960, but as in Engardt et al (2017) the meteorology of 1900-1959 had to be approximated by assigning random years from 1960 to 1969. This procedure introduces some uncertainty of course, although Langner et al (2012b) show that for the period from 1990 to 2100 it is emissions change, rather than meteorological change, that drives modelled O 3 concentrations.…”
Section: Forcing Datasetsmentioning
confidence: 99%
“…This set-up (EMEP + RCA3) is also used by Langner et al (2012a), Simpson et al (2014a), Tuovinen et al (2013), Franz et al (2017) and Engardt et al (2017), in which further details and model evaluation can be found. Unfortunately, the threedimensional RCA3 data needed by the EMEP model were not available prior to 1960, but as in Engardt et al (2017) the meteorology of 1900-1959 had to be approximated by assigning random years from 1960 to 1969. This procedure introduces some uncertainty of course, although Langner et al (2012b) show that for the period from 1990 to 2100 it is emissions change, rather than meteorological change, that drives modelled O 3 concentrations.…”
Section: Forcing Datasetsmentioning
confidence: 99%
“…As in Andersson et al (2007), boundary values representative of the average concentrations at the lateral and top boundaries of relevant species are interpolated spatially with a monthly temporal resolution. Boundary concentrations of O 3 , oxidized nitrogen and methane are furthermore scaled to mimic observed changes in the hemispheric background during the period 1990 through 2013 following the work of Engardt et al (2017);see Fig. 2a.…”
Section: Meteorology and Boundary Concentrationsmentioning
confidence: 99%
“…Elevated O 3 concentrations are formed in the troposphere by the oxidation of volatile organic compounds (VOCs) and carbon monoxide (CO), driven by solar radiation in a polluted air mixture that includes nitrogen oxides (NO x , sum of nitric oxide and nitrogen dioxide: NO + NO 2 ). Close to combustion sources, the background O 3 concentrations are reduced through reactions with directly emitted NO (see for example Finlayson-Pitts and Pitts, 2000). However, further away from the source and with sufficient availability of VOCs and under favorable weather conditions these NO x emissions can lead to rises in the O 3 concentration.…”
Section: Introductionmentioning
confidence: 99%
“…During the 20 th century, sulfur (S) deposition, which peaked in the 1980s, was the primary source of acidification in the acidic forest soils of the northern hemisphere (van Breemen et al, 10 1984). However, now that S deposition has dropped to around the 1930s level throughout Western Europe (Bertills et al, 2007;Engardt et al, 2017), focus has shifted towards understanding forest soil dynamics in response to forest biomass production and different harvesting scenarios (Akselsson et al, 2007;Iwald et al, 2013;de Jong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%